KINETIKA REAKSI DAN KOMPOSISI KESETIMBANGAN GASIFIKASI BATUBARA KALIMANTAN TIMUR DENGAN UAP AIR MENGGUNAKAN KATALIS NIKEL KARBONAT - , Yudha Dwi P. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Kalimantan Timur coal as a potential source of syngas production through steam gasification process studied by analyzing reaction kinetics and equilibrium composition. The catalyst used is nickel carbonate (NiCO3) were added to the coal char particles. Gasification experiment were conducted with coal char obtained after pyrolysis with a particle size of 4 to 5.6 mm at a temperature of 700Â°C, 800oC, and 900oC for 90 minutes. Sample of gases produced from reactor were taken from produced gases every 20 minutes and analyzed using Gas Chromatography (GC). The results indicate that the use of higher gasification temperature can increase the volume of the gases and also conversion of coal char. The use of nickel carbonate as a catalyst can increase the volume of gas produced but does not provide changes to the coal conversion at the same temperature. The increase in the catalytic conversion of coal gasification maximum of 2% occurs at a temperature of 900oC. Gasification reaction kinetics model were analyzed using Volumetric Model (VM), Shrinking Unreacted Core Model (SUCM), and Random Pore Model (RPM). The results of the analysis showed that Random Pore Model (RPM) is a model that is closest to the experimental data with SSE of 6.6079. This result indicates that there is a complex mechanism in the gasification reaction and can not be approximated by a simple model. Equilibrium composition analysis performed using known chemical reactions approach and can fit experimental data for the entire gasification gas composition only at a temperature of 700Â°C. This is due to a decrease in gas temperature in reactor above coal bed, causing the formation of equilibrium at lower temperatures.